Development of a 3D ultrasound guidance system for permanent breast seed implantation. Issue 8 (10th July 2018) - Michael, Justin; Morton, Daniel; Batchelar, Deidre; Hilts, Michelle; Crook, Juanita; Fenster, Aaron
Abstract : Purpose: Permanent breast seed implantation (PBSI) is a promising radiotherapy technique for early‐stage breast cancer, completed in a single visit by permanently implanting 103 Pd seeds using needles inserted through a template and guided by two‐dimensional (2D) ultrasound (US). However, operator dependence has been highlighted as a limitation of this procedure. Consequently, we propose and have developed an intraoperative guidance system using three‐dimensional (3D) US and an instrumented mechanical arm to provide intraoperative 3D imaging and needle template tracking. Methods: A mechatronic 3D US scanner reconstructs a 3D image from 150 2D images. A tracked mechanical arm mounted to the scanner locates four fiducial points on the template, registering the template to the 3D image. 3D reconstruction was validated for linear and volumetric measurement accuracy using phantoms of known geometry. In vivo breast US image quality was evaluated in a healthy volunteer. The encoded arm was calibrated and validated using a jig with divots at known locations relative to the scanner and the scanner registered to the 3D US image using intersecting strings in a fluid‐filled test jig. Template registration accuracy was assessed using a machined test jig. Tracking accuracy was assessed in a liquid medium by comparing tracked and imaged needle tip positions. Finally, the system was used to guide a mock procedure in a patient‐specific phantom and micro‐CT imaging used to evaluate its accuracy. Results: Geometric validation showed median distances within ±1.1% of expected values and volumetric validation showed differences of ≤4.1%. Tracking arm point measurements showed an average error of 0.43 mm and 3D US volume registration showed target registration error ≤0.9 mm. Mean template registration accuracy in each axis of translation/rotation was ≤1.3 mm/1.0°. Mean needle‐targeting error was 2.5 mm and 1.6° for needle tips and trajectories, respectively. Mean needle tip and angular errors of the phantom procedure were 2.1 mm and 2.6°. Modeled seed displacement of the phantom procedure showed mean error of 2.6 mm and a maximum of 3.8 mm. Conclusions: A 3D US guidance system for PBSI has been developed. Benchtop performance and image quality in volunteer scans are satisfactory. A phantom PBSI procedure was successfully delivered using the system with maximum seed error within dosimetric benchmarks (<5 mm). Translation of the device into the clinic is forthcoming.